Epistemology of Islamic Education in the View of Muhammad Sholeh Darat - Wahid Arbani; Khoiruddin Nasution; Dardiri Hasyim (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
The method used to know the epistemology of Muhammad Sholeh's educational thought is carried out through three main elements, namely: riyadhoh (spiritual practice), maqamat (stages of Sufistic ascent), and ahwal (Sufism experience). Riyadhah is an exercise of the soul in truth and sincerity in the context of istiqomah in worshiping Allah SWT. The mental training carried out in this guidance process is as exemplified and carried out by the Prophet Muhammad SAW. There are three forms of riyadhoh that can be done by a student to get to know Allah SWT through three activities, namely; seeking knowledge, being consistent with the practice of the sunnah, and always maintaining time.